Characterization of high efficiency neutron detector linear arrays - Henderson, Christopher M. Jr. (Kansas State University, 2009)
Two types of high efficiency neutron detector arrays (HENDAs), a 32-channel planar device and two trenched devices, were constructed at Kansas State University (KSU) and characterized. These HENDAs are prototypes for a detector that will be developed for the Spallation Neutron Source (SNS), which is located at Oak Ridge National Laboratory (ORNL). The general design objectives of a proposal from the KSU Semiconductor Materials and Radiological Technologies (SMART) Lab to the National Science Foundation, which led to a grant that funded this research, were reached. A spatial resolution for the HENDA prototypes of approximately 120 μm was achieved. The prototypes had relatively fast response times of approximately 1.2 μs, with rise times of 300 ns for the planar device and 200 ns for the 100-μm deep trenched device. The thermal neutron counting efficiency of one of the trenched devices was measured to be about 12%. It is expected that the goal of a 50% efficient HENDA is attainable by making trenches contained within the trenched device deeper and by stacking modules in a sandwich design. The pulse heights produced by the HENDA prototypes were approximately 0.5 volt with noise levels of 13 mvolt, resulting in a signal to noise ratio of almost 40:1. The response of HENDA, when placed in the neutron beam from the tangential beam port of the KSU TRIGA Mark II was proportional to the reactor power from 2 kW to 512 kW. At 512 kW, the neutron flux is φ = 1.08x10[superscript]7 cm[superscript]-2 s[superscript]-1, and therefore HENDA can operate with negligible dead time at neutron fluxes beyond 107 cm-2 s-1. From the experimental results, HENDA is a valuable linear array detector and can be applied to experiments that are designed to study material properties and structures through methods such as neutron diffraction and imaging.
Keywords: detectors; neutron; semiconductor; Engineering, Nuclear (0552)